2008
DOI: 10.1038/bjp.2008.336
|View full text |Cite
|
Sign up to set email alerts
|

Etomidate reduces glutamate uptake in rat cultured glial cells: involvement of PKA

Abstract: Background and purpose: Glutamate is the main excitatory neurotransmitter in the vertebrate CNS. Removal of the transmitter from the synaptic cleft by glial and neuronal glutamate transporters (GLTs) has an important function in terminating glutamatergic neurotransmission and neurological disorders. Five distinct excitatory amino-acid transporters have been characterized, among which the glial transporters excitatory amino-acid transporter 1 (EAAT1) (glutamate aspartate transporter) and EAAT2 (GLT1) are most i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 58 publications
2
12
0
2
Order By: Relevance
“…By inhibiting PKC, upregulation of astrocyte glutamate uptake is prevented, which may unmask the effects of signaling molecules activated in astrocytes by afferent stimulation that acutely depresses astrocyte glutamate uptake. Cultured studies suggest that Gs GPCRs and activation of PKA downregulate glutamate uptake (Adolph et al 2007;Rath et al 2008). In future studies, it will be interesting to determine the potential role of PKA in modulation of astrocyte glutamate uptake in intact tissue preparations.…”
Section: Discussionmentioning
confidence: 99%
“…By inhibiting PKC, upregulation of astrocyte glutamate uptake is prevented, which may unmask the effects of signaling molecules activated in astrocytes by afferent stimulation that acutely depresses astrocyte glutamate uptake. Cultured studies suggest that Gs GPCRs and activation of PKA downregulate glutamate uptake (Adolph et al 2007;Rath et al 2008). In future studies, it will be interesting to determine the potential role of PKA in modulation of astrocyte glutamate uptake in intact tissue preparations.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in rats have shown that β 2 subunits seem to be preferentially located on GABAergic interneurons (Nishimura et al, 2005), and excessive activation of these receptors could cause disinhibition of cortical activity and seizures. Finally, in cultured astrocytes, etomidate can inhibit glutamate uptake, increasing the extracellular glutamate concentration such that it can spill over the synaptic cleft and activate extrasynaptic receptors, consequently increasing irritative activity (Räth et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Por último, como tercera posibilidad, el etomidato también actuaría disminuyendo la actividad de los transportadores de glutamato (EAAT, del inglés excitatory aminoacid transporter). En concreto, se ha observado que esta disminución de la actividad de recaptación se da en los EAAT del tipo 1 y 2, que se encuentran en los astrocitos [27,28]. La presencia de etomidato en concentraciones clínicas produce una disminución en la capacidad de recaptación de estos EAAT hasta del 40% [27].…”
Section: Discussionunclassified
“…En concreto, se ha observado que esta disminución de la actividad de recaptación se da en los EAAT del tipo 1 y 2, que se encuentran en los astrocitos [27,28]. La presencia de etomidato en concentraciones clínicas produce una disminución en la capacidad de recaptación de estos EAAT hasta del 40% [27]. Una de las funciones que realizan los astrocitos consiste en la recaptación de glutamato [3], y la disminución de esta actividad permitirá un aumento de la permanencia del glutamato en la hendidura sináptica, lo que permite incrementar la hiperexcitabilidad neuronal.…”
Section: Discussionunclassified